1998
DOI: 10.1099/00221287-144-1-137
|View full text |Cite
|
Sign up to set email alerts
|

Seroreactive species-specific lipooligosaccharides of Mycobacterium mucogenicum sp. nov. (formerly Mycobacterium chelonae-like organisms): identification and chemical characterization

Abstract: Strains of the new species Mycobacterium mucogenicum exhibit physiological and biochemical features very similar to those of the other species of the Mycobacterium fortuitum complex. To define taxonomic criteria for easy identification of M. mucogenicum, the glycolipid patterns of the reference strains and of 32 environmental and clinical isolates were examined by TLC. It was concluded that all M. mucogenicum strains of smooth colony morphology contained species-specif ic alkali-labile glycoconjugates. Three d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…T type II isolates exhibited only 0.6% partial rpoB gene sequence divergence with the region described by Kim et al (30). However, only one isolate has been described as M. mucogenicum ATCC 49650 T , whereas a large collection of M. mucogenicum isolates was more closely related to M. mucogenicum ATCC 49651 by cell wall analysis (45); likewise, our data confirm that the vast majority of M. mucogenicum isolates are closely related to the latter strain, suggesting that M. mucogenicum ATCC 49651 could become the type strain for this species. In our study, isolate D13, recovered from an bronchial aspirate, exhibited 1.7% divergence with M. septicum and was the second clinical strain of this emerging species (26,53).…”
Section: Discussionmentioning
confidence: 86%
“…T type II isolates exhibited only 0.6% partial rpoB gene sequence divergence with the region described by Kim et al (30). However, only one isolate has been described as M. mucogenicum ATCC 49650 T , whereas a large collection of M. mucogenicum isolates was more closely related to M. mucogenicum ATCC 49651 by cell wall analysis (45); likewise, our data confirm that the vast majority of M. mucogenicum isolates are closely related to the latter strain, suggesting that M. mucogenicum ATCC 49651 could become the type strain for this species. In our study, isolate D13, recovered from an bronchial aspirate, exhibited 1.7% divergence with M. septicum and was the second clinical strain of this emerging species (26,53).…”
Section: Discussionmentioning
confidence: 86%
“…In most cases in which the structural basis of colonial variations was investigated, it was found that rough morphotypes were devoid of some free glycolipids that were present in the smooth morphotypes. For example, it has been reported that in Mycobacterium kansasii and Mycobacterium mucogenicum the smooth and rough colony morphologies differ in the presence of trehalose-containing lipooligosaccharides, which are only present in smooth colony surfaces (Belisle and Brennan 1989;Mun˜oz et al 1998). Most Mycobacterium avium complex isolates segregate into smooth-transparent-, smooth-opaque-and rough-colony variants (Moehring and Solotorovsky 1965;Vestal and Kubica 1966;Schaefer et al 1970;Reddy et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The NCTC strain is a stable rough variant of the original smooth strain isolated by Stanford and Paul (Stanford and Paul 1973;Stanford et al 2004). Since it has been reported that in the genus Mycobacterium differences in colonial morphologies are directly related to different contents of surface exposed antigens (Barrow and Brennan 1982;Belisle and Brennan 1989;Mun˜oz et al 1998), we believed that it would be interesting to study whether the immunomodulatory properties of smooth and rough colony variants of M. vaccae were the same or presented differences. Therefore, in the present work we have studied the growth conditions in which smooth M. vaccae ATCC 15483 T switches to a rough phenotype; the biochemical and microscopic surface differences between both variants, and the immunological response elicited by mice immunised with smooth or with rough morphotypes.…”
Section: Introductionmentioning
confidence: 98%
“…LOSs were found and described in Mycobacterium kansasii (6 -8), Mycobacterium gastri (8,9), Mycobacterium szulgai (10), Mycobacterium malmoense (11), Mycobacterium gordonae (12), Mycobacterium butyricum (13), Mycobacterium mucogenicum (14), the Canetti variant of Mycobacterium tuberculosis (15) and, more recently in Mycobacterium marinum (Mma) (16). However, they remain among the less studied mycobacterial glycolipids at a biosynthetic, structural, and functional point of view.…”
mentioning
confidence: 99%